EXPLORING THE KALAMKARI THROUGH HAND-PAINTED TEXTILE ART - Gollapalle, Preethi; Kota, Dileep Kumar; Kumar, Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian calligraphy, or kalamkari, is a highly regarded traditional art form whose elaborate hand-painted motifs on textiles have attracted art fans for years. This paper delves into the intricate world of Kalamkari, a traditional Indian art form celebrated for its hand-painted textile artworks. The study aims to uncover Kalamkari’s historical evolution, cultural significance, and contemporary relevance through a multidimensional exploration. The methodology combines a thorough literature review, field study, visual analysis of artworks, and comparative examination across regions and historical periods. The literature review provides insights into Kalamkari’s origins, techniques, and socio-cultural contexts, while field study involves interactions with artisans and documentation of their techniques and processes. Visual analysis scrutinizes motifs, colours, and narrative elements in Kalamkari textiles, illuminating their aesthetic and symbolic dimensions.